Pengembangan Modul Edukasi Pendidikan Agama Islam bagi Orangtua dan Tokoh Masyarakat dalam Mengatasi Perilaku Negatif Remaja - Nikma, Nova Artha; Erawadi, Erawadi; Hasibuan, Zainal Efendi (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2025)
Negative behaviors among teenagers—such as fighting, alcohol abuse, and criminal activity—are increasingly prevalent and have become a matter of public concern. This trend reflects a weakness in character education and a lack of influence from religious education, particularly from parents and community leaders. This study aims to develop an Islamic Religious Education (PAI) educational module for parents and community leaders to address negative youth behaviors in Paran Napa Dolok Village, Barumun Barat Subdistrict, Padang Lawas Regency. The research method used is Research and Development (R&D) based on the 4D model: Define, Design, Develop, and Disseminate. The results indicate that the developed module is